Sub arachnoid block for emergency cesarean section in a pituitary dwarf - Zaman, AM; Islam, M; Chowdhury, KK; Rickta, D; Ireen, ST; Russel, TA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):119-122 The abstract of this article is available on the PubMed website